Recent advances in site-selective functionalization of carbohydrates mediated by organocatalysts. (1st January 2019) - Blaszczyk, Stephanie A.; Homan, Timothy C.; Tang, Weiping
Abstract: As one of the four fundamental building blocks of life, carbohydrates assume varied and expansive roles in biological contexts. More in-depth understanding of carbohydrates and their interactions, however, is often restricted by our inability to synthesize and subsequently functionalize them in a site-selective manner. This review will summarize recent advances in the site-selective functionalization of carbohydrates using organocatalysts, including achiral catalysts, chiral nucleophilic bases, chiral N-heterocyclic carbenes, and chiral phosphoric acids, with an emphasis on the catalytic nature in each case. As in many endeavors, taking an alternative approach can often lead to success, and selected examples of these achievements will be highlighted as well. Graphical abstract: Highlights: This review summarizes recent advances in the site-selective functionalization of carbohydrates using organocatalysts.